Menganalisis Kasus Penyuapan dalam Moral Kristiani dan Ditinjau dari Ensiklik Yohanes Paulus II Ut Unum Sint - Yosef Usman (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
The focus of this paper is to describe the case of bribery at the Supreme Court, Ex-Commissioner of Wika Beton Charged with 11 Years and 5 Months in Prison that occurred on Wednesday, February 14, 2024 - 15:05 and the emphasis of the case is on Christian moral rules and norms. The aim is to provide a brief panorama of the synopsis of the case and the moral issues raised in the case.  In addition, the author looks first at the general principles and ways of evaluating moral acts in a specific theory (fontes moralitas), followed by an analysis of the rules and norms of Christian morality and an assessment of the rules and norms of Christian morality.  The methods used in this article are literature study and case study, namely by looking at the overall explanation of the lectures in class, looking at the diktat of fundamental moral theology two, books related to Christian morals, and articles from journals.  The author found that in reality, some people do not live according to the rules and norms that apply in society. Some people consider rules and norms only as symbols in an institution. This means that humans are immersed in the comfort or enjoyment of their position, so there is a tendency to bribe or extortion or even arbitrary corruption.  Here there is a conclusion or virtue (Arete) from the case that the church does not turn a blind eye to the actions of Christians against all the crimes that take turns either in days, months or years. The church continues to pay attention to the rules and norms that occur in Christian moral life, so Pope John Paul II issued an encyclical entitled “Ut Unum Sint” (May 25, 1995). This encyclical discusses the Catholic Church's commitment to ecumenism, the fruits of dialogue, how far we have to go, and a recommendation. In addition, it is not only about corruption but also includes the issue of bribery or extortion.AbstrakPenulis meletakkan fokus tulisan ini menganalisis kasus suap menyuap yang dilakukan di  Perkara MA, Eks Komisaris Wika Beton  yang dituntut 11 Tahun 5 Bulan Penjara yang terjadi pada Rabu 14 Februari 2024 - 15:05.Tujuannya adalah penulis mau memberikan panorama singkat sinopsis kasus dan persoalan moral yang muncul dalam kasus tersebut dengan melihat terlebih dahulu prinsip umum dan cara penilaian perbuatan moral secara khusus “teori (fontes moralitas)” dan dilanjutkan dengan analisis “aturan dan norma moral” serta memberi penilaian dari sisi aturan dan norma dalam moral Kristiani. Metode yang digunakan dalam artikel ini  ini adalah studi kasus yaitu dengan melihat keseluruhan teologi moral Kristiani, buku-buku terkait moral Kristiani, dan artikel jurnal.  Penulis menemukan bahwa dalam kenyataannya sebagian manusia hidup tidak sesuai teori (fontes moralitas) dan  “aturan dan norma” yang berlaku dalam masyarakat. Sebagian orang lagi menganggap aturan dan norma hanya sebagai lambang dalam sebuah instansi. Dari situasi ini, maka ada tendensi untuk menyuap, pungli atau bahkan korupsi seenaknya. Kesimpulan dari kasus tersebut bahwa Gereja tidak menutup mata terhadap tindakan orang Kristiani terhadap segala kejahatan yang silih berganti baik dalam hari, bulan atau tahun. Gereja terus memperhatikan aturan dan norma yang terjadi dalam kehidupan moral Kristiani maka Paus Yohanes Paulus II mengeluarkan ensiklik yang berjudul “Ut Unum Sint” (25 Mei 1995). Dalam ensiklik ini persoalan yang dibahas komitmen Gereja Katolik terhadap ekumenisme, buah-buah dialog, dan masih berapa jauhkah perjalanan kita?, dan sebuah anjuran. Selain Itu juga bahkan bukan hanya persoalan korupsi saja melainkan termasuk persoalan suap menyuap atau pungli itu.